Philosophy of Religion - Meister, Chad. author. aut Link
IX, 157 p.
Keywords: Philosophy of Religion provides an engaging analysis of the current state of play in philosophy of religion, focusing on several central issues in the field. It is inclusive in its approach and designed for students, but it will also be useful to scholars and others seeking such an evaluation and interpretation of this field.